Brill' s Companion to the Reception of Homer from the Hellenistic Age to Late Antiquity - Manolea, Christina - Panagiota, (Brill's Companions to Classical Reception ;, 2021)
Brill's Companion to the Reception of Homer from the Hellenistic Age to Late Antiquity presents a comprehensive account of the afterlife of the Homeric corpus. Twenty chapters written by a range of experts in the field show how Homeric poems were transmitted, disseminated, adopted, analysed, admired or even criticized across diverse intellectual environments, from the late 4th century BCE to the 5th century CE. The volume explores the impact of Homer on Hellenistic prose and poetry, the Second Sophistic, the Stoics, some Christian writers and the major Neoplatonists, showing how the Greek paideia continued to flourish in new contexts.